SEXUAL MINORITIES: ASSESSMENT AND ANALYSIS PROBLEMS - Mikhail V. Karmanov (Статистика и экономика)
On a number of the objective and subjective reasons statistical information onprevalence of sexual minorities in societycauses very inconsistent estimates. Thus activity of sexual minorities predeterminesin recent years need of deep judgmentand the analysis of behavior and activityof the persons having nonconventionalsexual orientation.